2021
DOI: 10.3389/fneur.2021.668363
|View full text |Cite
|
Sign up to set email alerts
|

Increased Postoperative Fasting Glucose Is Associated With Unfavorable Outcomes in Patients Treated With Mechanical Thrombectomy Treatment

Abstract: Background and objective: Hyperglycemia on admission was associated with worse clinical outcomes after mechanical thrombectomy (MT) of acute ischemic stroke (AIS). We evaluated whether increased postoperative fasting glucose (PFG) was also related to poor clinical outcomes in patients who underwent MT treatment.Methods: Consecutive patients with large vessel occlusion underwent MT in our center were included. Admission glucose and fasting glucose levels after MT treatment were evaluated. Primary outcome was 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Hyperglycemia is a common and essential therapeutic target in acute ischemic stroke with and without premorbid diabetes. 1 , 2 Recent studies found the variability of glucose after stroke onset, or mentioned as glucose fluctuation, was an independent risk factor for poor outcomes as well as the glucose level, 3–6 with underlying mechanisms including increased oxidative stress, aggravated inflammation, endothelial impairment and microcirculation dysfunction. 6–8 It is also recommended to avoid glycemic excessive fluctuation or hypoglycemia in patients with acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia is a common and essential therapeutic target in acute ischemic stroke with and without premorbid diabetes. 1 , 2 Recent studies found the variability of glucose after stroke onset, or mentioned as glucose fluctuation, was an independent risk factor for poor outcomes as well as the glucose level, 3–6 with underlying mechanisms including increased oxidative stress, aggravated inflammation, endothelial impairment and microcirculation dysfunction. 6–8 It is also recommended to avoid glycemic excessive fluctuation or hypoglycemia in patients with acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The combined findings of a shorter onset to puncture time, shorter procedure times, and a higher rate of successful recanalization in the EM+ group indicate that a pre-existing non-disabling EM may impact the patient benefit from the EVT. Older age (18,19) and higher systolic blood pressure on admission (20,21) in the EM+ group may in part contribute to the unfavorable outcomes. Also, we hypothesize that the structural and functional changes caused by the contralateral EM, combined with the responsible focus for index stroke, may damage the bilateral brain tissues and may impair the reserve and recovery capacity.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, random blood glucose is susceptible to a variety of factors, like intake of food rich in sugar and medicine like hypoglycemic agents [ 9 ] et al Fasting blood glucose is less affected by food and drugs and almost every patient was tested after admission. FBG could partly reflect stress response resulting from the interaction of hormones with concomitant insulin resistance during acute diseases [ 9 , 25 ]. To some extent, it could reflect the influence of EVT on blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, it could reflect the influence of EVT on blood glucose. Only a few studies indicate that increased fasting blood glucose rises the risk of adverse functional outcome after EVT [ 7 , 8 , 9 , 25 ]. A retrospective cohort study found that there was a shift towards worse functional outcome in patients with increased fasting glucose levels, and impaired fasting glucose (glucose level above 5.5 mmol/L) was associated with poor functional outcome or death and with sICH during hospitalization [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation